Pediatric hypereosinophilic syndrome associated with liver damage, portal vein, splenic vein and superior mesenteric vein thromboses: a case report - Hai-Tao Zheng; Yan Xu; Xiao-Yu Yan; Yong-Bin Yan; Shu-Xia Ma; Ling-Ling Liu; Qian-Yi Zhao (BMC Pediatrics, 2023)
Abstract Background The hypereosinophilic syndrome (HES) is a group of rare blood disorders characterized by persistent eosinophilia and damage to multiple organs. HES can be either primary, secondary or idiopathic. Secondary HES are commonly caused by parasitic infections, allergic reactions or cancer. We described a pediatric case of HES associated with liver damage and multiple thrombi. Case summary A 12-year-old boy with eosinophilia was complicated with severe thrombocytopenia, liver damage, portal vein, splenic vein, and superior mesenteric vein thromboses. The thrombi recanalized after treatment with methylprednisolone succinate and low molecular weight heparin. No side effects appeared after 1-month. Conclusions Corticosteroids should be used at an early stage of HES to prevent further damage to vital organs. Anticoagulants should be recommended only in cases with thrombosis which should be actively screened as a part of evaluation of end organ damage.